Workers of the hospital maintenance sector: protection, hearing symptoms and noise exposure - Flávia Elisa Antunes Lemes de Oliveira Ramos (Revista CEFAC)
ABSTRACT Purpose: to investigate the use of hearing protection and symptoms in hospital maintenance workers and evaluate the noise level of the machines. Methods: a cross-sectional quantitative study held with workers from a public hospital maintenance service. A questionnaire related to personal, clinical and occupational history was used. Measurement of the noise level of the machines in the sector was carried out using a sound pressure level meter. Results: 57 male workers participated, mean age of 43.28 years, among the workers, carpentry prevailed (10.53%), length of time at the job averaged 8.9 years and 9.3 daily work hours; 45.76% did not know what could be done to reduce maintenance noise; 59.65% wore hearing protectors at work, ear plug model (47.37%), and 82.45% thought that the noise was reduced when they wore the hearing protector correctly. Auditory and non-auditory signs and symptoms were denied by most workers. Noise perception in the maintenance service was medium (53%) and high (44%), evidenced noise levels of 62.0 to 101dB (A). Conclusion: the hearing protector was worn by 59.7% of the workers, the plug model was the most used (47.4%) and 75.8% reported that occupational noise decreased with the use of hearing protectors. Most workers use hearing protection and have no hearing symptoms. However, the presence of symptoms such as otalgia (8.8%), otorrhea (5.3%), dizziness (14.0%), tinnitus (17.5%) and difficulty in speech comprehension (7, 0%) should be pointed out. Noise assessment showed high levels from some maintenance machinery, representing a risk for hearing. The sectors of the woodwork and metalwork were the noisiest.